2022
DOI: 10.1002/asmb.2678
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting portfolio returns with skew‐geometric Brownian motions

Abstract: The gist of this work is to propose a minimum tracking error portfolio that could be adopted not only as an automated alternative to ETFs but, it could also be potentially used to anticipate market changes in the target index. This goal has been achieved by adopting skew Brownian motion as a general framework.The proposed solution has been declined in two versions: the case in which the constituents (i.e., in our case the subindices) of the objective portfolio are uncorrelated among each other, and the case in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For the analysis, we have considered both real data and a simulated Brownian motion for comparison (for a connection between macroeconomic business cycles, determinism, and financial stochastic Ornstein-Uhlenbeck process, see Orlando et al [59]). The former refers to USA equities, and the latter is a signal commonly used in finance to model a stochastic process y t such as the Ornstein-Uhlenbeck process [60] dy t = −ϕ y t dt + σ dB t where ϕ > 0 and σ > 0 are some parameters and B t denotes a standard Brownian motion [61][62][63][64].…”
Section: Datamentioning
confidence: 99%
“…For the analysis, we have considered both real data and a simulated Brownian motion for comparison (for a connection between macroeconomic business cycles, determinism, and financial stochastic Ornstein-Uhlenbeck process, see Orlando et al [59]). The former refers to USA equities, and the latter is a signal commonly used in finance to model a stochastic process y t such as the Ornstein-Uhlenbeck process [60] dy t = −ϕ y t dt + σ dB t where ϕ > 0 and σ > 0 are some parameters and B t denotes a standard Brownian motion [61][62][63][64].…”
Section: Datamentioning
confidence: 99%
“…In particular, the inclusion of the normal law and the shape parameter regulating the skewness, allows for a continuous variation from normality to non-normality (see Azzalini, 2021). Recently, Bufalo et al (2022) described an application to forecasting portfolio returns with skew-geometric Brownian motions in presence of cross dependency between assets.…”
Section: On Skewed Distributions Of Returnsmentioning
confidence: 99%
“…Mandelbrot (Mandelbrot & Van Ness, 1968) was the first to apply fractional Brownian motion to natural time series for modeling strong interdependence between distant samples. A more recent approach can be found in Bufalo et al (2022). In the case of natural disasters, however, it has been experimentally found that the Hurst exponent is around 0.24 which “indicates that these time series are fractal and relatively long‐term” antipersistent (Jin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%